2006
DOI: 10.1158/0008-5472.can-06-1217
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Overexpression by Soft Tissue Sarcoma Cells: Implications for Tumor Growth, Metastasis, and Chemoresistance

Abstract: To better elucidate the role of vascular endothelial growth factor (VEGF) 165 in soft tissue sarcoma (STS) growth, metastasis, and chemoresistance, we generated stably transfected human STS cell lines with VEGF 165 to study the effect of VEGF 165 on STS cells in vitro and the effect of culture medium from these cells on human umbilical vascular endothelial cells. Severe combined immunodeficient mice bearing xenografts of transfected cell lines were used to assess the effect of VEGF overexpression and the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 33 publications
1
52
0
Order By: Relevance
“…[28][29][30] In a leiomyosarcoma cell line, critical roles of VEGF in growth and metastasis have been demonstrated. 31 In a large series of soft-tissue sarcomas, Yudoh et al 28 demonstrated that higher VEGF levels in tumor tissue were correlated with higher tumor stage and grade, increased risk of local and distant tumor recurrence, and poor overall survival, whereas Chao et al 32 failed to demonstrate any relationship between VEGF expression and patients' outcome. In our results, higher VEGF mRNA expression was also correlated with poor prognosis in the group of MNRCT.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] In a leiomyosarcoma cell line, critical roles of VEGF in growth and metastasis have been demonstrated. 31 In a large series of soft-tissue sarcomas, Yudoh et al 28 demonstrated that higher VEGF levels in tumor tissue were correlated with higher tumor stage and grade, increased risk of local and distant tumor recurrence, and poor overall survival, whereas Chao et al 32 failed to demonstrate any relationship between VEGF expression and patients' outcome. In our results, higher VEGF mRNA expression was also correlated with poor prognosis in the group of MNRCT.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry was performed as previously described (27). Briefly, paraffin sections were dewaxed and rehydrated before antigen retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical importance of angiogenesis in human tumors has been shown in several reports indicating a positive relationship between the blood vessel density in the tumor mass and poor prognosis with chemoresistance in patients with various cancers (7)(8)(9). Furthermore, recent reports showing that anticancer agents were less active against VEGF-overexpressing tumors (10,11) may support the idea that low-molecular drugs are not so effective in the treatment of solid tumors which are rich in blood vessels.…”
Section: Nk012 Suppresses Renal Cancer Progressionmentioning
confidence: 92%